SOCIALLY ADEQUATE CONDUCT AS PETTY CRIME - Stajnko, Jan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: the main objective of this contribution is to show that the notion petty crime is a complex concept which can, at least in part, be understood in the light of the doctrine of social adequacy. Methods: dogmatic method (methods of classification, description and compilation) as well as axiological method were used in the study of the notion petty offence and the doctrine of social adequacy. Results: factual and normative criteria extracted from the doctrine of social adequacy can have a profound impact on the understanding of the notion of petty crime. Discussion: because it impacts the concept of petty crime, understanding of Welzel's substantive criteria for social adequacy of conduct is crucial for lawgivers, criminologists and judges alike.